THE VIGOR AND VIABILITY TESTS OF BITTI (Vitex cofassus Reinw. ex Blume) SEEDS USING WATER IMMERSION TREATMENT IN A GREENHOUSE - Nurdayanti, Siti; Mukrimin, Mukrimin; Millang, Syamsuddin; Sultan, Sultan; Hasanuddin, Hasanuddin (Indonesian Journal of Forestry Research, 2025)
Bitti (Vitex cofassus Reinw. ex Blume) is a group of plants in the Verbenaceae family. The species is classified as a promising endemic plant in South Sulawesi; however, it has received little attention and has not been used and developed optimally. The seed is a recalcitrant category, which has responses to water loss. This study aimed to determine the effect of water temperature and storage periods on the vigor and viability of Bitti seeds. The study was conducted at a greenhouse of the Faculty of Forestry, Hasanuddin University, from May to July 2022. The design of the research was a Completely Randomized Design (CRD) consisting of two factors: water immersion temperature and storage time. Each treatment consists of 30 seeds, with three replications. The results showed that a water immersion temperature of 50°C with a storage period of two weeks gave the best results in the parameters of percentage of sprouts (65,55%), germination viability (65,55%), and mean germinated seeds per day (0,49). The water immersion temperature of 90°C, which was drained for 24 hours without storage, showed the highest value for the mean germination time parameter (31,1), and the soaking temperature of 90°C drained for 24 hours with one week of storage produced gave the best value for the vigor index parameter (4,77). It is considered that germination activities on Bitti seeds require treatment with suitable water immersion. Thus, Bitti seed germination activities require water immersion at a certain temperature and storage time.